Development of Cholesterol Calculator Websites: Investigation on Food Cholesterol in Malaysia Using Web-Based Calculator: Cholesterol Web-Based Calculator - Chu, Chun Chuan; Muhammad Basri, Cik Sri Mazzura (Enhanced Knowledge in Sciences and Technology, 2021)
In this research, we are interested in creating a cholesterol calculator website to help people calculate their cholesterol from dietary intake. We study and apply the programming tools required in website development such as Firebase, HTML, CSS, and JS. We collect the cholesterol data from particular food in Malaysia, and we use collected data to construct a website database by using JSON afterward. We ensure the cholesterol calculator website's performance and function are well before publishing it to the public on the internet. Lastly, we will discuss the result based on the website performance and observe a user's eating pattern through their food cholesterol data save on the website.